If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x+8=-4x+2
We move all terms to the left:
-6x+8-(-4x+2)=0
We get rid of parentheses
-6x+4x-2+8=0
We add all the numbers together, and all the variables
-2x+6=0
We move all terms containing x to the left, all other terms to the right
-2x=-6
x=-6/-2
x=+3
| r^2+9=17 | | 7b+9−4=9b−9 | | B=180-y | | 2(3+5n)=-2n+18 | | 5k–8=7 | | 5x+1=8x+ | | -20k=-400 | | -5(-y+19)-13y=-4y-19 | | 55.2=b/8 | | 5+3x-x=21 | | 125-55=x | | -2(10w-10)+5w=-14w-18 | | 18+y=37 | | .15=2000x+3300 | | 8(3^6-2x)=40 | | 8x+10=73° | | 76=10x-44 | | -2(1x-6)=-6 | | 2x²+6x+√(7)=±11 | | 2=d−8 | | 4(-8-7x)=80 | | -4(-6+x)=28 | | 76=10x-40 | | 5(4+6x)=320 | | 7(-6-3x)=42 | | -2(8x-9)=-12x+18 | | 7(6+5x)=-238 | | -6(-4x+4)=240 | | D=t^2-8t+7 | | -3(10-2x)=-42 | | -2(-3x+8)=-22 | | 7(2-x)=-14 |